Comparison of apical sealing between the Tagger hybrid technique and lateral condensation technique with different sealers - Belu Ccori Peña; Luis Adrian Mejía Gonzáles; Luis Alexander Orrego-Ferreyros (Mashhad University of Medical Sciences, 2024)
Objective: This study aimed to compare the effectiveness of the Tagger technique and the lateral condensation technique with different obturation cements in achieving optimal apical sealing in endodontic treatments.Methods: An in vitro study was conducted on 68 extracted human upper or lower first premolars. Teeth were randomly divided into four experimental groups (n=17) based on two obturation techniques and endodontic sealers employed, as follows: Group 1, Tagger technique with the zinc oxide-eugenol sealer; Group 2, Tagger technique with the resin-based sealer; Group 3, lateral condensation technique with zinc oxide-eugenol sealer, and Group 4, lateral condensation technique with resin-based sealer. Homogeneity of the gutta-percha mass and apical obliteration were evaluated under a digital stereomicroscope. Data were analyzed using the chi-square test, and a P-value<0.05 was considered statistically significant.Results: Most group specimens exhibited non-homogeneous gutta-percha, whereas apical obliteration was achieved in a significant proportion of samples across all groups. No significant difference was found between the study groups either in the homogeneity of the gutta-percha mass (P=0.978) or in the optimal apical obliteration (P=0.782).Conclusions: The study found no significant difference in the effectiveness of the Tagger hybrid and lateral condensation techniques using different sealers in achieving optimal apical sealing and gutta-percha homogeneity. This highlights the critical role of the clinician's expertise in ensuring successful endodontic outcomes.